Biological features and cultivation of sesame (a review) - N. V. Kishlyan; M. Sh. Asfandiyarova; Y. V. Yakusheva; A. G. Dubovskaya (Труды по прикладной ботанике, генетике и селекции)
Sesame is an ancient oilseed crop grown throughout the arid and subarid climates. Sesame oil has a good taste and is appreciated for its beneficial properties. The genus Sesamum L. (Pedaliaceae Lindl.) includes up to 38 species. The only cultivated species is S. indicum L. (2n = 26). It is grown in areas located between 45° N and 45° S. South Africa is considered the homeland of S. indicum. Sesame seeds contain 50–63% of oil, 25–27% of protein, 20% of carbohydrates, and are sources of such micronutrients as copper, calcium, iron, magnesium, zinc, vitamins A, B1, C and E. Sesame seeds and oil are used not only in the food industry but also in medicine. Sesame meal is a good animal feed. Recently, thanks to the deciphering of the sesame nuclear genome and the development of various genomic resources, including molecular markers for qualitative and quantitative characters, molecular breeding has become possible for such agronomic traits as high oil content and its composition, drought resistance, resistance to waterlogging, disease resistance, and high yield. The world production of sesame seeds according to FAO estimates for 2019 was about 7 million tons. The largest cropping areas are located in Africa, India, and China. In Russia, sesame can be grown in southern regions: Krasnodar and Stavropol Territories, Rostov and Astrakhan Provinces. Breeding work on sesame was carried out at the All-Union Research Institute of Oil Crops, where cultivars resistant to bacterial blight and Fusarium wilt were developed. Currently, sesame breeding programs are absent in Russia. There are over 25,000 sesame accessions in the world’s genebanks, including about 1,500 accessions in the VIR collection.